The Role of the Anglican Church in the Development of Nigerian Indigenous Language - Adetunmbi, Moses Adebolu; Adeleke, Olujobi Adeyemo; Iortyom, Mbazendan; Adejuwon, James Ayoola; Oluwajana, John; Olakanmi, John; Omoyayi, Samuel Olayinka (International Journal of Managemen Analytics (IJMA), 2024)
This study looks at the significant roles the Anglican Church's has played and commitment to education, translation, worship, publishing, and research has significantly impacted the development of Nigerian indigenous languages. The study was based on historical fact, books and other secondary sources of information, the conclusion and recommendations were based on the research findings.